Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/1348-0421.12922
|View full text |Cite
|
Sign up to set email alerts
|

cydA, spdC, and mroQ are novel genes involved in the plasma coagulation of Staphylococcus aureus

Abstract: Coagulation is a critical pathogenic process in Staphylococcus aureus. Although the agglutination of S. aureus has been studied for a long time, the genes involved in this process are not completely clear. We performed tube agglutination and dynamic turbidimetry tests to identify novel genes involved in reduced plasma coagulation. A total of 15 genes were identified, including coa, clfA, vwbp, saeS, agrA, trpC, spdC, mroQ, cydA, qoxC, sucC, pyrP, menH, threonine aldolase, and truncated transposase for IS1272. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Adding to the uncertainty, a recent study has even suggested that MroQ might hydrolyze the AIP, leading to the downstream inactivation of AgrC and by extension agr QS. 38 Our biochemical studies clarify this picture by firmly establishing a direct role for MroQ in the second step of AIP biosynthesis, at least for agr groups I and II. Moreover, we see no evidence that the enzyme metabolizes the mature AIP.…”
Section: In a Key Pair Of Studies Cosgriff Et Al And Marroquin Et Al ...mentioning
confidence: 58%
See 1 more Smart Citation
“…Adding to the uncertainty, a recent study has even suggested that MroQ might hydrolyze the AIP, leading to the downstream inactivation of AgrC and by extension agr QS. 38 Our biochemical studies clarify this picture by firmly establishing a direct role for MroQ in the second step of AIP biosynthesis, at least for agr groups I and II. Moreover, we see no evidence that the enzyme metabolizes the mature AIP.…”
Section: In a Key Pair Of Studies Cosgriff Et Al And Marroquin Et Al ...mentioning
confidence: 58%
“…However, these investigators stopped short of assigning a specific biochemical role for the protein, leaving it unclear whether the protease is directly involved in AIP maturation, or plays some other function in the agr signaling circuit, for example by modulating AIP sensing. Adding to the uncertainty, a recent study has even suggested that MroQ might hydrolyze the AIP, leading to the downstream inactivation of AgrC and by extension agr QS ( 38 ). Our biochemical studies clarify this picture by firmly establishing a direct role for MroQ in the second step of AIP biosynthesis, at least for agr groups I and II.…”
Section: Discussionmentioning
confidence: 99%
“…Coa acts as a mechanical barrier against phagocytosis by promoting plasma coagulation during infection. [27] In a previous study, only a few recruited white blood cells were found to engulf Staphylococcus in the abdominal cavity. This finding suggests that staphylococcus coagulation/clumping might provide a hypothesis for staphylococcus escape phagocytosis and clearance.…”
Section: Salicin Inhibits Coagulation In S Aureusmentioning
confidence: 94%